Biogeography and genetic diversity of clinical isolates of Burkholderia pseudomallei in Sri Lanka. - Himali S Jayasinghearachchi; Enoka M Corea; Kumari I Jayaratne; Regina A Fonseka; Thilini A Muthugama; Jayanthi Masakorala; Ravija Yc Ramasinghe; Aruna D De Silva (Public Library of Science (PLoS), 2021)
Background Melioidosis is a potentially fatal infectious disease caused by Burkholderia pseudomallei and the disease is endemic in Southeast Asia and Northern Australia. It has been confirmed as endemic in Sri Lanka. Genomic epidemiology of B. pseudomallei in Sri Lanka is largely unexplored. This study aims to determine the biogeography and genetic diversity of clinical isolates of B. pseudomallei and the phylogenetic and evolutionary relationship of Sri Lankan sequence types (STs) to those found in other endemic regions of Southeast Asia and Oceania. Methods The distribution of variably present genetic markers [Burkholderia intracellular motility A (bimA) gene variants bimABP/bimABM, filamentous hemagglutinin 3 (fhaB3), Yersinia-like fimbrial (YLF) and B. thailandensis-like flagellum and chemotaxis (BTFC) gene clusters and lipopolysaccharide O-antigen type A (LPS type A)] was examined among 310 strains. Multilocus sequence typing (MLST) was done for 84 clinical isolates. The phylogenetic and evolutionary relationship of Sri Lankan STs within Sri Lanka and in relation to those found in other endemic regions of Southeast Asia and Oceania were studied using e BURST, PHYLOViZ and minimum evolutionary analysis. Results The Sri Lankan B. pseudomallei population contained a large proportion of the rare BTFC clade (14.5%) and bimABM allele variant (18.5%) with differential geographic distribution. Genotypes fhaB3 and LPSA were found in 80% and 86% respectively. This study reported 43 STs (including 22 novel). e-BURST analysis which include all Sri Lankan STs (71) resulted in four groups, with a large clonal group (group 1) having 46 STs, and 17 singletons. ST1137 was the commonest ST. Several STs were shared with India, Bangladesh and Cambodia. Conclusion This study demonstrates the usefulness of high-resolution molecular typing to locate isolates within the broad geographical boundaries of B. pseudomallei at a global level and reveals that Sri Lankan isolates are intermediate between Southeast Asia and Oceania.